ENAM KEKUATAN LAYANAN JASA INTERNET BANKING: TINJAUAN DARI PERSEPSI NASABAH - Ronny, Ronny (LPPM Universitas Terbuka, 2017)
The banking problem studied is the kind of strength which is become the base of services in the field of internet banking. The study was conducted by analyzing the consumers perception in the 5 variables of service quality consist of security, reliability, responsiveness, physical ability, and collateral. As much as 10 informants who are users of internet banking of bank in Indonesia has been interviewed about their perceptions of the quality of internet banking services. This study uses qualitative approach. The analysis showed that there are 6 strength that underlies the quality of internet banking services namely communication, channel of customer participation, service facilities, human resources, technology infrastructure and norms. The sixth strength of the internet banking service is a dimension of strength to compete in the banking industry. Masalah bank yang diteliti adalah kekuatan apa yang menjadi landasan layanan jasa di bidang internet banking. Penelitian dilakukan dengan menganalisis persepsi nasabah pada 5 variabel kualitas layanan yakni keamanan, keandalan, responsif, kemampuan fisik, dan jaminan. Sebanyak 10 informan yang merupakan pengguna internet banking dari bank di Indonesia telah diwawancarai mengenai persepsi mereka terhadap kualitas layanan internet banking. Penelitian ini menggunakan pendekatan kualitatif. Hasil analisis menunjukkan bahwa terdapat 6 kekuatan yang melandasi kualitas layanan jasa internet banking yakni komunikasi, saluran partisipasi nasabah, fasilitas layanan, sumber daya manusia, infrastruktur teknologi dan norma. Keenam kekuatan layanan internet banking tersebut merupakan dimensi kekuatan bersaing dalam industri perbankan.